The Impact of the Quality of Tourism Services Provided by Small and Medium Enterprises on Tourist Satisfaction in North Al Sharqiya Governorate, Sultanate of Oman - Tashtoush, Hayel AbdElmawla; Al-Maskariyah, Yusra Amer Suleiman; Al-Harthiyah, Rahma Salem Abdullah; Al-Zuwaidiyah, Jokha Salem Shannan; Al-Maskariyah, Asya Yusuf Mohammed (Journal of Economic, Administrative and Legal Sciences, 2025)
This study aimed to examine the impact of the quality of tourism services provided by small and medium enterprises on tourist satisfaction in the North Sharqiyah Governorate of Oman. The study focused on five dimensions of tourism service quality (tangibility, security, responsiveness) as an independent variable and tourist satisfaction as a dependent variable. A questionnaire was used as a quantitative tool for data collection, with a total of 203 responses. The descriptive analytical approach was applied using Excel to address the research questions and hypotheses.The study results indicated that the current level of tourism service quality in North Sharqiyah Governorate, Oman, was rated as high. Similarly, the overall level of tourist satisfaction with tourism services in the governorate was also high. Regarding the specific dimensions of tourism service quality, the findings revealed a statistically significant impact of the dimensions tangibility and responsiveness on tourist satisfaction. However, the security dimension did not show a statistically significant effect on tourist satisfaction, indicating that it is not a key factor influencing tourists' perceptions of service quality. This suggests that other factors may have a greater impact on the level of tourist satisfaction.
Keywords: Tourism service quality; small and medium enterprises; tourist satisfaction; North Sharqiyah Governorate